2013
DOI: 10.1094/cchem-07-12-0079-r
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Deficit Irrigation on Maize Physical and Chemical Properties and Ethanol Yield

Abstract: Cereal Chem. 90(5):453-462The objective of this research was to study the effect of irrigation levels (five levels from 102 to 457 mm of water) on the physical and chemical properties and ethanol fermentation performance of maize. Twenty maize samples with two crop rotation systems, grain sorghum-maize and maize-maize, were harvested in 2011 and evaluated at the Kansas State University Southwest Research-Extension Center near Garden City, Kansas, under a semiarid climate. Results showed that maize kernel weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…The low viscosities under drought treatment are probably due to the decreased granule size, crystallinity, and swelling power , given that the large granules possess a loose packing ability, occupy a relatively larger volume, and are less stable toward shearing compared with the small granules at similar concentrations. Some studies also observed that drought decreased the pasting characteristics of cassava starch , sorghum starch , normal, and waxy maize flour . By contrast, Singh et al observed that the wheat starch peak viscosity was increased by water stress when the percentage of large granules was increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low viscosities under drought treatment are probably due to the decreased granule size, crystallinity, and swelling power , given that the large granules possess a loose packing ability, occupy a relatively larger volume, and are less stable toward shearing compared with the small granules at similar concentrations. Some studies also observed that drought decreased the pasting characteristics of cassava starch , sorghum starch , normal, and waxy maize flour . By contrast, Singh et al observed that the wheat starch peak viscosity was increased by water stress when the percentage of large granules was increased.…”
Section: Resultsmentioning
confidence: 99%
“…The vol% of the starch granules with diameters lower than 5 mm was slightly affected, whereas that for large granules (with the peak point as the boundary) was evidently reduced by water deficit in both varieties. Previous studies showed that drought reduces granule size in cassava [29], wheat [30], barley [31], and normal maize [11]. The small starch granule size is probably due to the fact that drought suppresses the development of starch granules, decreases the grain filling rate, and shortens the grain filling duration [32].…”
Section: Starch Granule Sizementioning
confidence: 99%
“…Other authors have reported different results. For example, Liu et al [22] did not note any significant difference in the grain oil content of maize grown with different levels of irrigation. Considering the effect of drought stress on the grain oil content of summer maize, Ge et al [3] stated that moderate drought increased and that strong drought decreased the oil content.…”
Section: Oilmentioning
confidence: 96%
“…Research conducted by Lu et al [21] in China showed that water deficit had no effect on the starch content of fresh waxy maize. Liu et al [22] reported that the starch content of the grain samples of maize grown with less irrigation was 3.0% smaller than with high irrigation levels.…”
Section: Starchmentioning
confidence: 99%
“…Oktem (2008) observed that water deficit decreases some mineral element (Fe, Cu, and Zn) contents but increases the protein content in sweet maize grains. Liu et al (2013) observed that maize starch granule size and viscosities decrease and gelatinization temperatures increase under low irrigation levels. Our previous studies showed that high temperature, weak light, and drought after pollination significantly deteriorated the quality of waxy maize starch (Lu, Cai, Zhao, Shen, & Lu, 2015;Lu, Sun, Wang, Yan, & Lu, 2013;Lu et al, 2014).…”
Section: Introductionmentioning
confidence: 97%